Pengaruh Pendapatan Asli Daerah, Dana Perimbangan, dan Lain-lain Pendapatan Daerah yang Sah Terhadap Belanja Daerah Kabupaten/Kota di NTB Periode 2014–2023 - Gerindra Maulana Saputra; Helmy Fuadi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to “analyze the influence of Regional Original Income, Balancing Funds, and Other Legitimate Regional Income on Regional Expenditure in regencies/cities in West Nusa Tenggara Province during the period 2014–2023.” The type of research applied is quantitative research through a causal associative approach. The data used is secondary data with panel data type sourced from the Directorate General of Fiscal Balance of the Ministry of Finance. The data analysis technique applied is panel data regression with the help of Eviews 12. The existing findings describe “partially Regional Original Income, Balancing Funds, and Other Legitimate Regional Income have a positive and significant effect on Regional Expenditure in regencies/cities in West Nusa Tenggara Province during the period 2014–2023.” Then, “simultaneously the three variables also have a significant effect on Regional Expenditure in regencies/cities in West Nusa Tenggara Province during the period 2014–2023.”